2013
DOI: 10.2478/s11756-013-0167-5
|View full text |Cite
|
Sign up to set email alerts
|

Changes in photosynthesis, chlorophyll fluorescence, and antioxidant enzymes of mulberry (Morus ssp.) in response to salinity and high-temperature stress

Abstract: Photosynthesis, chlorophyll (Chl) fluorescence, and antioxidant enzymes were measured in the mulberry (Morus spp.) cultivars Da 10, Hongguo 2, Anza 1, and Taiwan 72C002, which were subjected to salinity and high-temperature stress (STS; 0.1%, 0.3%, and 0.5% NaCl concentrations, 34.5• C day/night temperatures). Control plants were watered with 1 L of full-strength Hoagland's nutrient solution with no added NaCl. Net photosynthetic rate (PN), stomatal conductance (gs), and effective quantum yield of photosystem … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 42 publications
3
8
0
Order By: Relevance
“…Here, we determined the activities of four antioxidant enzymes (CAT, APX, SOD and GR) to investigate the response of K. pygmaea to the complex environment along an increasing elevational gradient. The results agreed with previous reports that some antioxidant enzyme activities were induced by low temperature, UV radiation or some other types of stresses [28] [31] . We observed that all four enzyme activities exhibited similar increasing trends ( Figure 3 ), which were consistent with the results related to another alpine herb, Potentilla saundersiana [5] .…”
Section: Discussionsupporting
confidence: 93%
“…Here, we determined the activities of four antioxidant enzymes (CAT, APX, SOD and GR) to investigate the response of K. pygmaea to the complex environment along an increasing elevational gradient. The results agreed with previous reports that some antioxidant enzyme activities were induced by low temperature, UV radiation or some other types of stresses [28] [31] . We observed that all four enzyme activities exhibited similar increasing trends ( Figure 3 ), which were consistent with the results related to another alpine herb, Potentilla saundersiana [5] .…”
Section: Discussionsupporting
confidence: 93%
“…The dissipation of excitation energy, determined as NPQ, is one of the ways that most photosynthetic mechanisms resist the adversity (Misra, Latowski, & Strzalka, ). Increased NPQ in response to NaCl treatment was observed in several plants, such as Citrus reticulata seedlings (Khoshbakht, Ghorbani, Baninasab, Naseri, & Mirzaei, ) and Morus alba (Yu et al, ). The OJIP analysis of Spirulina platensis showed that the fluorescence yield of J, I and P phases decreased sharply with the increase of salt concentration, and qP decreased when qN increased (C. Lu & Vonshak, ).…”
Section: Photosynthetic Pigmentsupporting
confidence: 72%
“…In this study, the activities of all three enzymes increased consistently with increasing NaCl stress (0.1-0.3%), but we also found a reduction in antioxidant enzyme activities at high levels of NaCl stress. Similar results were found by Yu et al suggesting that 0.5% NaCl stress may cause inactivation of antioxidant enzymes or prevent the synthesis of enzymatic antioxidants in 1-year-old mulberry cultivars [11]; however, in their study, seedlings suffered not only salt stress, but also high temperature, and the influences of single salt stress on antioxidants were not clear.…”
Section: Discussionsupporting
confidence: 72%